HYDRAULIC PUMP CONTROLLER THROUGH IOT BY SENSING MOISTURE CONTENT IN SOIL - Reddy, B. Vishnuvardhan; T., Mani Mohan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This work proposes a system for controlling a pump through IoT by sensing soil moisture content in soil. The system aims to optimize water usage and improve plant growth by measuring the moisture content in soil and turning on/off the pump accordingly. The system consists of soil moisture sensor, Arduino uno, an IoT device, and a cloud-based server or a local computer. The Arduino UNO coded with some set of instructions it will take the data from system i.e, status of pump and soil. Arduino UNO passes the instruction to system to pump on/off to make soil wet/dry. The sensor measures the moisture content in soil. The Node MCU is connected with internet to transfer the data from system to server or user. The user can check the status of pump and soil by using thing cloud open software and the status displayed on system LCD display also.